Legal and Regulatory Development of Nuclear Energy in Bangladesh - Karim, Ridoan; Muhammad Sukki, Firdaus; Karim, Mohammad Ershadul; Munir, Abu Bakar; Sifat, Imtiaz; Abu Bakar, Siti Hawa; Bani, Nurul Aini; Muhtazaruddin, Mohd Nabil (MDPI, 2018)
The adequacy of legal and regulatory framework relating to nuclear energy in Bangladesh has sparked many questions since the government took the formal decision to establish a nuclear power plant (NPP) at Rooppur. Consequently, the government has taken some measures to make a comprehensive and robust framework to ensure safe and secure nuclear energy production in the country. Even though these initiatives are highly appreciable, there remain certain regulatory concerns which this paper has attempted to reflect. Therefore, the objective of this paper is to showcase the recent legal and regulatory development of Bangladesh in relation to nuclear energy and to recommend further developments. The study was based on secondary sources where a doctrinal research was carried out to solve particular research questions. The safety and security of the Rooppur Nuclear Power Plant will frankly rely on how the government of Bangladesh plans and learns to implement, design, safeguard, exchange and further develop nuclear energy related knowledge and talent around the country.